INCLUSIVE EDUCATION IN THE AGE OF TECHNOLOGY: BRIDGING ACCESSIBILITY AND EQUITY GAPS - Hana Gardenia Mahbubah; Abdun Wijaya (INJOSEDU: International Journal of Social and Education, 2026)
The development of digital technology has brought significant changes to the education system, including strengthening inclusive education practices oriented towards equal access and justice for all students. The research method used a literature review by reviewing various scientific articles, books, policy reports, and relevant academic publications on inclusive education, educational technology, and the issue of equal access to learning. The results of the study indicate that technology has the potential to increase the participation of students with special needs through the use of adaptive assistive devices, flexible learning platforms, artificial intelligence, and disability-friendly learning media. In addition, technology can also expand the reach of education for marginalized groups in remote areas through online learning systems and open learning resources. However, the effectiveness of its implementation is greatly influenced by teacher readiness, policy support, the availability of facilities, and the commitment of educational institutions to the principle of inclusivity.